2017
DOI: 10.1016/j.ultsonch.2017.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanism of diclofenac degradation in aqueous solution by US/Zn0

Abstract: A system of ultrasound radiation coupled with Zn was applied to degrade diclofenac. The effects of initial pH, dosage of Zn and ultrasound density were investigated. To further explore the mechanism of the microcosmic reaction, the fresh and used Zn powders were characterized by SEM, XRD and XPS. Radical scavengers were used to determine the oxidation performance of strong oxidizing free radicals on diclofenac, including hydroxyl radicals and superoxide radicals. The results showed that the optimum removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Proving the above statement, in the research carried out by Huang et al. 61 it was found that at a pH > 2 the degradation of DCF was very low, while at values equal to or less 2, the degradation of the tested compound reached percentages greater than 80 %. The authors concluded that this form actually favored the degradation and absorption of DCF by Zn0.…”
Section: Basic Principles Of Sonochemistrymentioning
confidence: 86%
See 1 more Smart Citation
“…Proving the above statement, in the research carried out by Huang et al. 61 it was found that at a pH > 2 the degradation of DCF was very low, while at values equal to or less 2, the degradation of the tested compound reached percentages greater than 80 %. The authors concluded that this form actually favored the degradation and absorption of DCF by Zn0.…”
Section: Basic Principles Of Sonochemistrymentioning
confidence: 86%
“…Under conditions where the pH is lower than the pollutant's acidity constant p K a , it is found in molecular form, whereas in pH > p K a the compound loses a proton and is negatively charged, presenting itself in ionized form. In sonochemical reactions, mass transfer through cavitation bubbles is facilitated in molecular nature, providing greater degradation of compounds by hydroxyl radicals in the film area and/or by thermal pyrolysis in gas bubbles 61, 62. Otherwise, the ionic type compound can be oxidized by hydroxyl radicals in the aqueous solution.…”
Section: Basic Principles Of Sonochemistrymentioning
confidence: 99%
“…Different authors have reported that the performance of the oxidation reactions in sonochemical treatments is associated with the effect of the chemically active cavitation, which is related to the effectiveness of the formation, growing and imploding of the cavitation bubbles and with the ability of the pollutant molecules to diffuse into the exterior and the interior of the bubble [21] , [22] . The implementation of US process should consider the control and variation of different operating parameters such as the solution pH, the applied US power and the ultrasonic frequency since they can promote the production of HO• [18] , [23] . In this sense, some preliminary tests were carried out to establish the experimental range of the solution initial pH and the applied US power that conduct to significant antibiotics eliminations (>50.0%).…”
Section: Methodsmentioning
confidence: 99%
“…The US process must consider the control and variation of the different operating parameters, including the ultrasonic frequency, the electrical power and the pH and temperature of the solution [46,47], in order to be optimized with the subsequent reduction in the costs associated with the process performance. The nature of the contaminant of interest and the constituents of the water matrix must also be considered during the US-assisted AOP optimization procedure since they are involved in the efficiency of the process.…”
Section: Efficiency Of the Ultrasound Processmentioning
confidence: 99%
“…Meanwhile, Huang et al [46] evaluated the degradation of DCF through US process in the presence of Zn 0 , performing an analysis of the influence of pH on this type of process. It was found that at pH higher than 2 the degradation of DCF was very small, while at equal or lower values, the degradation of the tested compound reached percentages higher than 80%.…”
Section: Solution Phmentioning
confidence: 99%